VD_FINDINFO HC / 2013 / 101 vom 16. Januar 2013 - VD Tribunal cantonal (2013)
BAIL À LOYER, DÉFAUT DE LA CHOSE, DROIT À LA RÉDUCTION DU PRIX | 259a al. 1 let. b CO, 259d CO, 274d al. 3 CO, 13 al. 1 OBLF, 16 OBLF, 247 al. 2 CPC (CH), 308 al. 2 CPC (CH)